Aplicação de jogos matemáticos no 1º ano do ensino médio - QUARESMA, Mário Antonio Mata (2022)
Despite the evolution of teaching that is currently taking place, mathematics continues to be one of the reasons for the large number of students failing, regardless of the level of education: elementary, high school or higher. The reasons given for this are diverse, but there is a general consensus that when teachers use different methods, leaving that traditional teaching posture, the final result improves a lot. For example, the use of math games is one of the alternatives that many educators use to improve students' performance in this subject, but there are still few teachers who use games in the classroom and when they do, it is more for elementary education than for high school. The present work aimed to show, through experience carried out in the classroom, with a class of the 1st year of high school, that it could apply math games to high school and that makes the learning performance increase. This work presents five games that already exist in the literature, which can be applied in high school, but in the application that took place in a school in the municipality of Abaetetuba, only one was used due to the time made available by the teacher. During the activity, it was possible to perceive a greater interest in learning the mathematical content to participate in the game. Several quotes were presented giving credit to the use of these games, so it is understood that it is valid to do these experiences in the classroom. The games proposed here are simple suggestions that can be used in schools, with practically zero cost. With the application of the game, it was concluded that the attempt is really valid to improve the "image" of this discipline feared by many, sometimes so hated and also much loved for its fascination when creating differentiated and dynamic teaching strategies ("lively" ). And above all, make sure that students don't leave the classrooms anymore, wasting the opportunity for a better future, which in most cases can only be achieved through education.